Interleukin-1 beta is significantly upregulated in the decidua of spontaneous and recurrent miscarriage placentas. (April 2021) - Löb, Sanja; Amann, Niklas; Kuhn, Christina; Schmoeckel, Elisa; Wöckel, Achim; Zati zehni, Alaleh; Kaltofen, Till; Keckstein, Simon; Mumm, Jan-Niclas; Meister, Sarah; Kolben, Thomas; Mahner, Sven; et al.
Highlights: IL-1β gene expression is 54-times higher in placental tissue of recurrent abortion compared to controls. Immunohistochemistry confirmed a significant upregulation of IL-1β in the decidua of recurrent miscarriage specimens. Double-immunofluorescence identified decidual stoma cells as IL-1β expressing cells. Decidual upregulation of IL-1β may be associated with an imbalanced maternal immune system in early pregnancy loss. Abstract: Background: Pregnancy is an extraordinarily complex immunological process. For successful pregnancy maintenance the maternal immune system must adapt to and tolerate the semi-allogenic fetus at the fetomaternal interface of the placenta. This balance is regulated by cytokines with a predominant T helper 2 (Th-2) system and a suppressed inflammatory T helper 1 (Th-1) response. This study investigates the role of the Th-1 pro-inflammatory cytokine Interleukin-1 beta (IL-1β) and its role in early pregnancy loss. Patients and methods: In order to identify differences in IL- β levels a TaqMan® Human Cytokine Network Array, with placental tissue obtained from patients with healthy pregnancies (n = 15) and recurrent miscarriage (n = 15), was carried out. Protein expression of IL-1 β in the decidua of healthy pregnancies (n = 15), spontaneous (n = 18) and recurrent miscarriages (n = 15), was investigated by immunohistochemistry. The identification of IL-1 β expressing cells in the decidua was done with double-immunofluorescence. Results: Gene expression analysis identified a nearly 54-times higher expression of IL-1 β in placental tissue of patients suffering from recurrent abortion. Immunohistochemistry confirmed a significant upregulation of IL-1 β in the decidua of recurrent miscarriage specimens (p = 0.01) as well as in the decidua of women with spontaneous abortion (p = 0.001). Double-immunofluorescence identified decidual stoma cells as IL-1 β expressing cells. Conclusion: Significant upregulation of IL-1β may be associated with an imbalanced immune system and a procoagulant state that could be responsible for early pregnancy loss. These results provide new evidence of the complex interplay of IL-1β at the fetomaternal interface and its crucial role in miscarriage processes.